Data-centric framework for digital twin development of an aircraft system - Singh, Sumit (Cranfield University, 2019)
Poster presented at Cranfield University’s 2019 Manufacturing Doctoral Community event.
Keywords: digital twin; DT; data modelling frameworks; MDC19 poster; Aerospace Engineering